EVALUATION OF ANATOMOPATHOLOGICAL, SEROLOGICAL, IMMUNOLOGICAL RESPONSES AND PROTECTION IN BROILERS VACCINATED WITH LIVE INFECTIOUS BURSAL DISEASE VACCINES - Nishizawa, M. [UNESP]; Paulillo, A.c. [UNESP]; Bernardino, A.; Alessi, A.c. [UNESP]; Sayd, S.; Okada, L.s.n. [UNESP]; Doretto, L (Instituto Biológico, 2022)
The study was divided into three experiments. In the first one, broilers were distributed into six groups and vaccinated against infectious bursal disease at 14 days of age: T1-not vaccinated, T2-Lukert1 (intermediate), T3-Lukert2 (intermediate plus), T4-228E, T5-V877 and T6-Winterfield 2512 (“hot” strains). Bursas of Fabricius (BF) were collected at 17, 21, 28 and 35 days to measure BF relative weight (BFRW), diameter, histological examination and image processing analysis (IPA). At one, 14, 21, 28 and 35 days of age, samples of blood taken from eight birds from each group for serology analysis by ELISA test. Hot strains vaccines induced reduction of BFRW and BF diameter, higher histological score lesion degree, more lymphocyte depletion on the BF follicles and higher IBD antibody titer. In the second experiment, 16 birds from groups T1 to T6 were isolated and challenged with a very virulent strain of IBDV (vvIBDV) at 25 days of age. Only groups T4, T5 and T6 were totally protected against vvIBDV challenge. In the third experiment, the immunosuppressive potential of each vaccine was determined by examining the ability of IBDVvaccinated birds to respond to Newcastle disease (ND) vaccination and challenge. None of the vaccines was found to be immunodepressive.

O estudo foi dividido em três experimentos. No primeiro, frangos foram distribuídos em seis grupos e vacinados contra a Doença Infecciosa da Bursa (IBD) aos 14 dias de idade: T1-não vacinados, T2-Lukert1 (intermediária), T3-Lukert2 (intermediária plus), T4-228E, T5-V877 e T6-Winterfield 2512 (cepa forte). As bursas de Fabrícius (BF) foram colhidas aos 17, 21, 28 e 35 dias para mensurar o seus pesos relativos da BF (BFRW), diâmetros, exames histológicos e processamento de imagem imagens(IPA). Ao primeiro, 14, 21, 28 e 35 dias de idade, foram colhidas amostras de sangue de oito aves de cada grupo para a realização de sorologia através do método ELISA indireto. As vacinas cepa forte induziram redução do BFRW peso e do diâmetro da BF, maior grau de lesão histológica e depleção linfocitária e títulos mais elevados de anticorpos. No segundo experimento, 16 aves dos grupos T1 ao T6 foram isoladas e desafiadas com o vírus muito virulento da IBD (vvIBDV) aos 25 dias de idade. Somente os grupos T4, T5 e T6 foram completamente protegidos do desafio com vvIBDV. No terceiro experimento, o potencial imunossupressor de cada vacina foi determinado através da capacidade das aves vacinadas responderem à vacinação contra a Doença de Newcastle (ND) e posterior desafio. Nenhuma vacina apresentou-se imunossupressora.
AVALIAÇÃO DAS RESPOSTAS ANATOMOPATOLÓGICA, SOROLÓGICA, IMUNONOLÓGICA E PROTETORA EM FRANGOS DE CORTE VACINADOS COM VACINAS VIVAS CONTRA A DOENÇA INFECCIOSA DA BURSA
Keywords: Infectious Bursal Disease; very virulent infectious bursal disease virus; live vaccines; bursa of Fabricius; broilers; immunosuppression; Doença Infecciosa da Bursa; vírus muito virulento; vacinas vivas atenuadas; bursa de Fabrícius; frangos de corte; imunossupressão